Bridging the architecture gap: Abstracting performance-relevant properties of modern server processors - Hofmann, Johannes; Alappat, Christie; Hager, Georg; Fey, Dietmar; Wellein, Gerhard (Supercomputing Frontiers and Innovations, 2020)
We propose several improvements to the execution-cache-memory (ECM) model, an analytic performance model for predicting single-and multicore runtime of steady-state loops on server processors. The model is made more general by strictly differentiating between application and machine models: an application model comprises the loop code, problem sizes, and other runtime parameters, while a machine model is an abstraction of all performance-relevant properties of a processor. Moreover, new first principles underlying the model's estimates are derived from common microarchitectural features implemented by today's server processors to make the model more architecture independent, thereby extending its applicability beyond Intel processors. We introduce a generic method for determining machine models, and present results for relevant server-processor architectures by Intel, AMD, IBM, and Marvell/Cavium. Considering this wide range of architectures, the set of features required for adequate performance modeling is surprisingly small. To validate our approach, we compare performance predictions to empirical data for an OpenMP-parallel preconditioned CG algorithm, which includes compute-and memory-bound kernels. Both single-and multicore analysis shows that the model exhibits average and maximum relative errors of 5 % and 10 %. Deviations from the model and insights gained are discussed in detail.
CRIS-Team Scopus Importer:2020-08-07
Keywords: AMD; Analytic modeling; ARM; Execution-cache-memory model; IBM; Intel; Microarchitecture comparison; Performance evaluation; Performance modeling